Charles S. Shepherd, The General Ordinances of the City of Saint Joseph 508 (1897) - (:unkn) unknown (My University, 1897)
§ 7: Prohibited the carrying of a concealed pistol or revolver, colt, billy, slungshot, cross knuckles or knuckles of lead, brass or other metal, dirk, dagger, razor, Bowie knife, or any knife resembling a Bowie knife, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED